Unlocking Creativity: Utilizing The 5 Whys Methodology to Illuminate Core Issues in Student Supreme Government - Almaden, Antoniette M.; Valle, Paula Trisha E.; Ursal, Din Emman S.; Cabanlit, Cheradee Ann M. (Future Science / FSH-PH Publications, 2024)
Student engagement programs served as catalysts for student development, community building, and active participation in campus life. This research explored the state of student engagement programs within the Supreme Student Government (SSG), focusing on their effectiveness and levels of student participation. Utilizing the 5 Whys methodology, the study identified and analyzed critical challenges and opportunities related to student motivation, program structure, and alignment with student interests. The findings revealed that internal communication breakdowns and budget constraints were significant factors impeding the effectiveness of SSG programs. Student participation was only moderate due to conflicting schedules with classes and insufficient program marketing. The rigid structure of SSG programs and a lengthy approval process further limited their ability to meet student needs. A disconnect between program content and student interests hindered engagement. The research concluded that the root causes of these problems lay in the need for more structured communication channels, a complex approval process, and misalignment with student interests. By addressing these underlying motives, recommendations included enhancing internal communication, allocating funds as efficiently as possible, and creating an inclusive learning environment. These strategies aimed to develop more effective and appealing student engagement programs, ultimately fostering a more active and engaged student body.